Specificity of language representation of the category of artistic time in works by A. Akhmatova (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
The article defines the specifics of the linguistic representation of the category of artistic time in the works by A. Akhmatova. It is revealed that in her poetic texts, the artistic and grammatical time are closely linked; artistic time is created by all elements of the text, including linguistic (temporal vocabulary, visual-time forms of the verb, syntactic constructions, etc.). Poems show different manifestations of time (domestic and historical time, personal and social time, physical and mythological time). The poet's attention is the image of time associated with the motives of movement, development, formation, with the contrasting transient and eternal.
Keywords: chronotope; artistic time; temporal vocabulary; poetic text; A. Akhmatova